Field monitoring study of an integral abutment bridge supported by prestressed precast concrete piles on soft soils. (1st December 2015) - Kong, B.; Cai, C.S.; Kong, X.
Highlights: A field monitoring program was conducted on an integral bridge. Temperature distributions, abutment displacements, etc. are measured. Daily and seasonal bridge thermal responses are discussed. Conclusions are drawn on the integral bridge performance. Abstract: Integral abutment bridges (IABs) have been constructed during the past several decades around the world. The purpose was to eliminate expansion joints and minimize joints induced problems. Even though IABs have been widely accepted due to the satisfying performances, yet they have not been largely applied in practice. Some of the reasons may be attributed to the uncertainties of these bridges under different loading conditions, especially the daily and yearly varying temperature effects. In this paper, the behavior of the first IAB constructed on the soft soil condition in Louisiana is discussed. A field monitoring program is introduced and the measured results from 08/11/2011 to 03/15/2014 are presented. The field monitoring program leads to the following observations, (1) significant seasonal and daily temperature variations are observed on the bridge slabs but within the AASHTO temperature design specification; (2) the displacements and rotations of bridge components are well correlated with the temperature variations; (3) the thermal stresses generated in the slabs may exceed the allowable material cracking capacity; (4) the soil behavior behind the abutments is complicated and long term monitoring program is needed; (5) the integral abutment primarily behaves in translation rather than rotation; and (6) the pile inflection (zero bending) point is observed and the strong and weak axels bending are all important due to the bridge skewness.